A Bibliometric Analysis of Materials Engineering Education: Trends and Their Implications for Research and Education - Ragadhita, Risti; Nandiyanto, Asep Bayu Dani (Bumi Publikasi Nusantara, 2024)
This paper critically examines the emerging trends, content evolution, and pedagogical innovations in materials engineering education. Using a systematic literature review approach, this study synthesizes key developments in materials engineering education focusing on enrolment trends in materials-related engineering disciplines and their implications for future research and educational practices. The result shows that the rapid technological, environmental, and industrial transformations of the 21st century have redefined the competencies required of materials engineers. As global challenges such as climate change, resource scarcity, digitalization, and sustainable development become more pressing, materials engineering education must undergo significant pedagogical and curricular reform to remain relevant. The findings aim to provide actionable insights for educators, policymakers, and curriculum developers in creating a responsive and sustainable materials engineering education system for the 21st century.